Legal Protection of Women Migrant Workers: A Bibliometric Analysis Review - Putro, Warsito Eko; Larasati, Endang Larasati; Wijayanto, Wijayanto; Yuwanto, Yuwanto; Ardiyansah, Ardiyansah (Al-'Adl, 2024)
The fourth Sustainable Development Goal (SDGs) is decent work and economic growth, which means that migrant workers around the world should have decent work and protection. In reality, there is no strong legal protection for migrant workers. Problems that arise against migrant workers such as more than 200 migrant workers who become domestic helpers in 18 countries are suspected of being victims of trafficking and exploitation of labour, prostitution or other forms of sexual exploitation, which means forced labour, slavery or similar practices, to the removal of organs. The method used in looking at the development of the phenomenon of migrant worker protection is carried out using the bibliometric analysis method. The software used is Vos Viewer (VOS) software. The results of this study provide knowledge and recommendations for readers and journal writers who can become references by adjusting the selected issues. This research highlights research trends on the Protection of Migrant Workers seen from the authors and journals that write the most about the phenomenon. The results of this study show that the writing of articles on the Protection of Migrant Workers fluctuates every year. The keywords that often appear in research on the Legal Protection of Migrant Workers are "Legal Protection", "Migrant Workers", "Indonesian Migrant Workers", "Human Rights" and "Trafficking". The government through international law needs to implement strong legal rules so that migrant workers get legal protection and a decent life.